(untitled) (Nepal Journal of Environmental Science, 2024)
In the mountainous regions of Nepal, springs are the primary source of freshwater for rural communities and also serve as unique habitats for endemic and threatened aquatic species, particularly macroinvertebrates that are excellent bioindicators of water quality. Therefore, a comprehensive assessment of benthic macroinvertebrates is imperative for species conservation before they face extinction. This study in Panchadewal Binayak Municipality focused on evaluating the community structure of Benthic Macroinvertebrates and identifying key environmental factors influencing them. A total of 25 springs and 4 streams were selected, all currently in use or with potential for future use. Altogether, 439 benthic macroinvertebrate individuals belonging to 32 families were observed, revealing high richness in Ephemeroptera, Plecoptera, and Trichoptera (EPT) taxa. Most springs were categorized as class II, indicating moderate pollution. Several environmental variables such as turbidity, dissolved oxygen, chloride, nitrate, sodium, iron, and potassium, significantly influenced the community structure. Human activities such as bathing, clothes washing, littering, livestock watering, and agricultural runoff were identified as major stressors. Although none of the springs were classified as critically degraded, the risk of deterioration remains high. This study emphasizes the importance of springs as habitats for a diverse group of benthic macroinvertebrates, providing valuable information for conservationists and resource managers. Informed decisions can now be made to protect these habitats and the associated services they provide in the Panchadewal Binayak Municipality.